Production and management of stone pine (Pinus pinea) for early nut production: grafted plantations as an alternative for restoring degraded areas and generating income in rural communities of Tunisia - Piqué M.; Ammari Y.; Solano D.; Aletà N.; Bono D.; Sghaier T.; Garchi S.; Coello J.; Coll L.; Mutke S. (Mediterranean stone pine for agroforestry, 2013)
We introduce a four years project (2008-2012), supported by the Program of Scientific Cooperation and Interuniversity Research (PCI), funded by the Spanish Agency for International Development Cooperation (AECID), and implemented in Tunisia and Spain. The objective of the project was to establish a systematic methodology for producing grafted plant using two types of stock: Pinus pinea and Pinus halepensis, from known provenances from Spain and Tunisia and to implement field trials in both countries, on different hydric and edaphic conditions, for evaluating the development of the plantations. Due to Pinus pinea interest for nut production, grafted Pinus pinea plantations for early and abundant cone yield can be an interesting alternative for restoring and revalorize some Mediterranean areas, generating both economic and ecological benefits (soil protection).
AGROPINE 2011 International Meeting on Mediterranean Stone Pine for Agroforestery, 2011/11/17-19, Valladolid (Spain)